Study on thermal protection and temperature of PMMA plastic optical fiber for concentrated sunlight transmission in daylighting. (15th March 2023) - Wang, Kai; Wang, Qian; Zou, Lianglin; Su, Ying; Liu, Kunhao; Li, Wei; Zhang, Kexin; Wang, Haiyu; Song, Jifeng
Highlights: Realization of high flux transmission via PMMA plastic optical fibers. Plastic optical fibers effectively avoid overheating under 4500 suns. Combination of IR filter and heat absorbing glass for 780–2500 nm filtering. Abstract: Daylighting system by concentrating and transmitting sunlight through optical fiber is an emerging technology of direct utilization of solar energy. In this work, a sunlight concentrating and transmitting system via plastic optical fibers was developed and investigated. This study addressed the overheating problem of plastic optical fibers under highly concentrated light irradiation. Polymethylmethacrylate (PMMA) plastic fibers have a strong absorption in the infrared band. The PMMA plastic fiber generates serious heat under highly concentrated light transmission, which leads to its overheating and burning. In this study, an incident light filtering method based on the combination of infrared filter and insulating glass is proposed. By filtering out the infrared band light with significant thermal effect, the PMMA plastic optical fibers are guaranteed to be within a safe working temperature range. Experiments demonstrated that the developed filter system can ensure the safe operation of PMMA plastic optical fibers at the concentration level of about 4300 suns. This shows that it is feasible to use low-cost plastic optical fiber for highly concentrated daylighting system.